Removal efficiency and reaction kinetics of phenolic compounds in refinery wastewater by nano catalytic wet oxidation - Yousif S. Issa; Khaleel I. Hamad; Rafi J. Algawi; Jasim Humadi; Sara Al-Salihi; Mustafa A. Ahmed; Ahmed A. Hassan; Abdul-Kareem Abd Jasim (International Journal of Renewable Energy Development, 2023)
A novel nano-catalyst based on iron oxide (MnO2/Fe2O3) was developed to promote wet oxidation of phenol. MnO2 was doped in Fe2O3 matrix to prepare composite nano-catalyst with different doping percentage (0, 2 and 5%). The catalytic phenol oxidation was conducted under different reaction temperatures and residence times. To evaluate the optimal kinetic parameters aiming to maximize phenol removal under the optimal conditions for the catalytic wet phenol oxidation process, modeling was applied on the batch reactor using the novel synthesis nano-catalyst (MnO2/Fe2O3) and the model developed was fed with the experimental data. gPROMS package was used to model the process of phenol oxidation and to optimize the experimental data. The error predicted between the simulated and experimental data was less than 5%. The optimal operating conditions were 294 min residence time, 70oC reaction temperature, and 764 ppm initial concentration of phenol over the prepared 5% MnO2/Fe2O3. Running of wet oxidation of phenol under the optimal operating conditions resulted in 98% removal of phenol from refinery wastewater.